Dynamic Response Analysis of Commuter Aircraft Windshield Under Drone Impact Using Finite Element Method - Noval Erlangga; Raihan Farhan Ramadhan (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2026)
This study investigates the dynamic response of a commuter aircraft windshield subjected to drone impact and compares its damage characteristics with bird-strike conditions. Numerical simulations were conducted using the finite element method (FEM), incorporating variations in impact location, angle, and velocity. The results show that both impact location and angle significantly affect damage severity. For location and angle variations, the drone penetrated the windshield, with the most severe damage occurring at the center location and a 0° impact angle, resulting in maximum energy absorption of 1573.98 J. The plastic strain area at the center and at 0° was wider than at the upper edge and 22.5°, respectively. For velocity variations, the highest absorbed energy of 1975.04 J occurred at 105.5 m/s. At 58 m/s, cracking occurred without penetration, while penetration occurred at 80 m/s and above. Despite its lower mass compared to a 910 g bird, the drone impact proved more hazardous due to windshield penetration.